The Referendum that Wasn't: Constitutional Recognition of Local Government and the Australian Federal Reform Dilemma. (2016) - Brown, A J; Kildea, Paul
In 2010, the Commonwealth government proposed Australia's third attempt to give federal constitutional recognition to local government. In 2013, the government secured the passage through Parliament of a Constitution Alteration but, due to political events, and amid much controversy, the proposed amendment was not put to the people. This paper examines the merits and prospects for success of the proposed reform, with an eye to lessons for the future of local government's place in the federal system. It argues that the legal and constitutional cases for the alteration were strong, but limited, and poorly contextualised, theorised and articulated. We use public opinion evidence to conclude that had it proceeded, the referendum result would probably have been a third failure. These lessons are important for ongoing debate over sub-constitutional and constitutional reform to Australian intergovernmental relations, including questions of federal financial redistribution at the core of the proposal. Overall, the events of 2013 reinforce arguments that reforms to the position of local government, while important, should only be pursued as part of a holistic package of federal reform and renovation; and that more robust deliberative processes and principles must be adhered to before again attempting any constitutional reform.